Trichloroethylene Degradation by Two Phenol Utilizing Strains of Comamonas testosteroni - Ruzicka, Jan; Dvorackova, Marie; Koutny, Marek (Asian Journal of Chemistry, 2011)
Environmental isolate Comamonas testosteroni RF2 and its derivative strain VM obtained by random chemical mutagenesis were tested for their capacity to degradation of trichloroethylene. Both strains were able to grow on lactate and phenol in the presence of trichloroethylene at concentrations from 0.8-50 mg/L and in the state of resting cells they were able to degrade trichloroethylene during ca. 22-24 h. Trichloroethylene degradation by both strains led to more than 95 % mineralization of chlorine. However, VM culture produced significantly higher amount of trichloroacetic acid (3.4 mol %) than maternal strain RF2 (0.15 mol %). Using lactate as the substrate and phenol as the inducer, it was possible to realize three consequent cycles of trichloroethylene degradation by strain RF2 under growing condition, with substantial regeneration of its degradation capacity.